The effect of inadvertent systemic hypothermia after mechanical thrombectomy in patients with large-vessel occlusion stroke - auf dem Brinke, Kristina; Kück, Fabian; Jamous, Ala; Ernst, Marielle; Kunze-Szikszay, Nils; Psychogios, Marios-Nikos; Maier, Ilko L. (Frontiers in Neurology, 2024)
Postinterventional hypothermia is a frequent complication in patients with large vessel occlusion strokes (LVOS) after mechanical thrombectomy (MT). This inadvertent hypothermia might potentially have neuroprotective, but also adverse effects on patients' outcomes. Aim of the study is to determine the rate of hypothermia in patients with LVOS receiving MT and its influence on functional outcome. Methods: We performed a monocentric, retrospective study using a prospectively derived databank including all LVOS patients receiving MT between 2015 and 2021. Predictive value of postinterventional body temperature and body temperature categories (hyperthermia (≥38°C), normothermia (35°C-37,9°C) and hypothermia (<35°C)) on functional outcome were analyzed using multivariable Bayesian logistic regression models. Favorable outcome was defined as modified Rankin Scale (mRS) ≤3. Results: Of the 480 included LVOS-patients with MT (46.0% men, mean±SD age 73±12.9 years), 5 (1.0%) were hyperthermic, 382 (79.6%) normothermic and 93 (19.4%) hypothermic. Postinterventional hypothermia was significantly associated with unfavorable functional outcome (mRS>3) after 90 days (OR 2.06, 95%CI 1.01-4.18, p=0.045). For short-term functional outcome, patients with hypothermia had a higher discharge NIHSS (OR 1.38, 95%CI 1.06 to 1.79, p=0.015) and a higher change of NIHSS from admission to discharge (OR 1.35, 95%CI 1.03 to 1.76, p=0.029). Conclusions: About a fifth of LVOS-patients in this cohort were hypothermic after MT. Hypothermia was an independent predictor of unfavorable functional outcome. Our findings warrant a prospective trial investigating active warming during MT.